The Effects of Grammar Mastery and Critical Thinking on Students’ Speaking Skill - Bayu Andika Prasatyo; Devian Try Gustary; Santosa Santosa (Indonesian Journal of Multidisciplinary Science, 2021)
The purpose of the research is to obtain empirical data and analyze about whether or not there are the effects of grammar mastery and critical thinking on students’ speaking skill. The reseach was conducted at the state senior high school in Serang. The research method was survey with multiple-correlation technique. 80 students out of the state senior high school, grade X were chosen to be samples. Data collections include 1 questionnaire and 2 multiple-choice tests. The scale used for questionnaire was Likert Scale. The validity was calculated by using Person-Product Moment, and reliability obtained from Cronbach Alpha is 0.713. Research findings show three points. Firstly, there are significant effects of grammar mastery and critical thinking towards students’ speaking skill where multiple-correlation coefficient (R) is 0.696 in significance grade 5% ( = 0,05) further Fobserved is higher than Ftable (36.202 > 2.735). Secondly, there was a significant effect of grammar mastery and students’ speaking skill even though the effect is slightly weak where ry1 is 0.365, tobserved=3.725>ttable=1.994 with Sig score is lower than significance grade (0.000 < 0.05). Thirdly, there is a significant effect of critical thinking and students’ speaking skill where ry2 is 0.626, tobserved=7.242>ttable=1.994 with Sig score lower than the significance value (0.000 < 0.05).